The value of a and b in given expression must be
respectively so that given equality becomes identity.
Solution:
Need to find the value of a and b in following expression so that following equality will become identity.
------- eqn 1
Lets Simplify Right hand Side first,
![(a)/((x+1))+(b)/((x-4))=(a(x-4)+b(x+1))/((x+1)(x-4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t75fk46e6a0nyl0m4br8564rd2qclzcv2f.png)
![\begin{array}{l}{=(a x-4 a+b x+b)/((x+1)(x-4))} \\\\ {=(a x+b x-4 a+b)/((x+1)(x-4))} \\\\ {=((a+b) x-4 a+b)/((x+1)(x-4))}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k89bcza7vgch2ocpton6jq2agnjz4k1k10.png)
![=>(a)/((x+1))+(b)/((x-4))=((a+b) x-4 a+b)/((x+1)(x-4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2ku0fhaiclyp8db4thegyanuo70693657f.png)
![\text {On substituting } (a)/((x+1))+(b)/((x-4))=((a+b) x-4 a+b)/((x+1)(x-4)) \text { in equation } 1 \text { we get }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o7q5ks860uh1f8wc2fd4jy8673bi5bh92g.png)
![((x-1))/((x+1)(x-4))=((a+b) x-4 a+b)/((x+1)(x-4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xmmphntd1jpqxsyyz78bgrsxqihao67ea1.png)
On multiplying both sides by (x+1)(x-4) we get
![((x-1))/((x+1)(x-4)) *(x+1)(x-4)=((a+b) x-4 a+b)/((x+1)(x-4)) *(x+1)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/85yw6qjt5enmp22qpt7bpm4q4f69j6k14f.png)
![\Rightarrow x-1=(a+b) x-(4 a-b)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n3gnwv1soj5acevr0d56z2064aqg1useym.png)
On comparing coefficient of x and constant term separately, we get
a + b = 1 and 4a - b = 1
On adding the two equations we get
a + b + 4a - b = 1 + 1
=> 5a = 2
=>
![a = (2)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hzys6jb3266hixxtwrz9oqh1gsebt9eepw.png)
![\text {Substituting } \mathrm{a}=(2)/(5) \text { in equation } a+b=1, \text { we get }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/knn7oiko0u0jnvmwo0ff2vlc4tiovj9mlr.png)
![\begin{array}{l}{(2)/(5)+b=1} \\\\ {\Rightarrow b=1-(2)/(5)=(3)/(5)}\end{array}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/28l1uo1wq065e9r7yi9852ud5ugiqowe02.png)
So the value of a and b in given expression must be
so that given equality becomes identity.